1996
DOI: 10.1246/cl.1996.407
|View full text |Cite
|
Sign up to set email alerts
|

Trichlorosilane-Dimethylformamide (Cl3SiH-DMF) as an Efficient Reducing Agent. Reduction of Aldehydes and Imines and Reductive Amination of Aldehydes under Mild Conditions Using Hypervalent Hydridosilicates

Abstract: Trichlorosilane-dimethylformamide (Cl3SiH-DMF) was found to be an effective reducing agent for reduction of aldehydes to alcohols, imines to amines, and also reductive amination of aldehydes. Hypervalent silicates are active species, which enable efficient reduction under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(71 citation statements)
references
References 13 publications
0
70
0
1
Order By: Relevance
“…The concept that neutral and anionic Lewis bases can promote the transfer of activated silyl nucleophiles to carbonyl substrates offers a useful alternative to the use of metal -based catalysts and was fi rst used by the group of Kobayashi for the reduction of aldimines with a trichlorosilane/DMF reagent [31] . This concept has also been widely used in the fi eld of asymmetric catalysis for various types of silyl nucleophiles, including allyl -, enol -, cyanide -and hydride -based reagents.…”
Section: Chiral Lewis Bases As Catalystsmentioning
confidence: 99%
“…The concept that neutral and anionic Lewis bases can promote the transfer of activated silyl nucleophiles to carbonyl substrates offers a useful alternative to the use of metal -based catalysts and was fi rst used by the group of Kobayashi for the reduction of aldimines with a trichlorosilane/DMF reagent [31] . This concept has also been widely used in the fi eld of asymmetric catalysis for various types of silyl nucleophiles, including allyl -, enol -, cyanide -and hydride -based reagents.…”
Section: Chiral Lewis Bases As Catalystsmentioning
confidence: 99%
“…The results obtained using 3a-f as activators are summarized in Table 1, which also shows the results using 1a-e for comparison. Although the yield of 5a in the absence of activators was low (entry 1), the reduction became more efficient by addition of a catalytic amount of N-formylpyrrolidines 1a-e (entries [2][3][4][5][6]. Similarly, compounds 3a-f were found to work as activators for Cl 3 SiH (entries 7-12).…”
Section: A 5amentioning
confidence: 99%
“…One of such reagents may be trichlorosilane (Cl 3 SiH), a liquid material easily available from silicon industry, 4 though some activator is necessary for Cl 3 SiH to efficiently reduce ketones and imines. 5 We already reported chiral N-formylpyrrolidine derivatives 1 as organic activators in the enantioselective reduction of ketones 6 and imines 7 with Cl 3 SiH. The reduction proceeds smoothly at room temperature with good yields and enantioselectivity of up to 43%ee…”
mentioning
confidence: 98%
“…Silanes are normally too unreactive for a direct hydride transfer to an unsaturated compound and the addition of a suitable mediator is necessary in order increase the reactivity. This is in particular true for the trichlorosilane (3) (see Figure 14.3 ) which requires activation by a Lewis base to release its hydride [23,24] . Matsumura and coworkers found that activating trichlorosilane with catalytic amounts of N -formylpyrrolidine derivatives resulted in the chemoselective reduction of imines [25,26] .…”
Section: Silanesmentioning
confidence: 99%